1991
DOI: 10.1111/j.1365-3016.1991.tb00727.x
|View full text |Cite
|
Sign up to set email alerts
|

Cohort reconstruction: which infants can be restudied at school age?

Abstract: Longer-term follow-up of infants with specific health concerns, such as low birthweight, is critical to assessing the effect of medical interventions. This report examines the approach of reconstructing previously studied cohorts in terms of the factors discriminating between respondents and non-respondents. Follow-up was attempted during 1987-1988 for 1875 children born during a 6-month period in 1978 in three geographically defined regions in the United States, for whom 1-year assessments of health and devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Difficulties experienced when tracing children include the breakup of families and the placement of the child with one parent or with another relative. Additionally, surname differences, possibly due to changes in the parents' marital status, add to the difficulty of tracing [5,6]. In our study, we found that parental information at the time of registration was generally accurate, and tracing was necessary only 15% of the time.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…Difficulties experienced when tracing children include the breakup of families and the placement of the child with one parent or with another relative. Additionally, surname differences, possibly due to changes in the parents' marital status, add to the difficulty of tracing [5,6]. In our study, we found that parental information at the time of registration was generally accurate, and tracing was necessary only 15% of the time.…”
Section: Discussionmentioning
confidence: 52%
“…The type of information used to trace subjects varies depending on the tracing method. Many studies employ credit agencies to find lost participants, where the full name of the subject and social security number is helpful for a successful search [5,6,10]. State and local vital records offices, departments of motor vehicles, and the National Death Index can also be used in tracing efforts [6,[10][11][12][13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Castro et al 14 and McCormick et al, 4 on the other hand, found that compared with children who were lost to follow-up, those who were compliant with follow-up had more adverse outcomes. It seems that the adolescents with higher completed or current education are overrepresented in the full-response group at the age of 19 years.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors suggest that nonresponse increases the proportion of infants with adverse outcomes in the remaining study population, and others have described the reverse. 4,5 We therefore used the opportunity presented to assess the influence of complete response, partial response, and nonresponse on the outcome measures of our follow-up study of 19-year-old adolescents who were born as preterm infants. …”
mentioning
confidence: 99%